Characterization of Metabolites during Biodegradation of Hexahydro-1,3,5-Trinitro-1,3,5-Triazine (RDX) with Municipal Anaerobic Sludge - Hawari, Jalal (American Society for Microbiology, 2000)
The biodegradation of hexahydro-1,3,5-trinitro-1,3,5-triazine (RDX) in liquid cultures with municipal anaerobic sludge showed that at least two degradation routes were involved in the disappearance of the cyclic nitramine. In one route, RDX was reduced to give the familiar nitroso derivatives hexahydro-1-nitroso-3,5-dinitro-1,3,5-triazine (MNX) and hexahydro-1,3-dinitroso-5-nitro-1,3,5-triazine (DNX). In the second route, two novel metabolites, methylenedinitramine [(O(2)NNH)(2)CH(2)] and bis(hydroxymethyl)nitramine [(HOCH(2))(2)NNO(2)], formed and were presumed to be ring cleavage products produced by enzymatic hydrolysis of the inner C—N bonds of RDX. None of the above metabolites accumulated in the system, and they disappeared to produce nitrous oxide (N(2)O) as a nitrogen-containing end product and formaldehyde (HCHO), methanol (MeOH), and formic acid (HCOOH) that in turn disappeared to produce CH(4) and CO(2) as carbon-containing end products.